Impact of the Islamic Modes of Finance on the Profitability of Islamic Banking Sector in Pakistan - Gul, Mudeeba; Khan, Atta Ullah (Islamic Banking and Finance Review, 2023)
The persistence of Islamic finance in any economy is arguably essential to address the economic needs of the society. The golden principles of Islam that is, profit and loss sharing, honesty, and doing business keeping in view the welfare of the people can play a vital role in alleviating poverty. The primary objective of the current study is to investigate empirically the impact of the Islamic modes of finance and their contribution in enhancing profitability. For this purpose, time series quarterly data ranging from 2014Q1-2020Q4 of the Islamic modes of finance (including Sukuk) were used to find their impact on the profitability of the Islamic banking sector as measured by Return on Asset (ROA). The ARDL and bounds cointegration approach were used to examine the level relationship among the underlying variables. The results provided strong evidence of a long-run equilibrium relationship. The results also showed that Murabaha, Musharaka, Istisnaa, and Diminishing Partnership have a prominent positive and significant impact on ROA. However, the impact of Murabaha on profitability remains significantly higher as compared to the other modes of finance. The second most important determinant of profitability is Musharaka, followed by Istisnaa. The estimated value of error correction term showed a significant adjustment towards the long-run equilibrium. These findings may help the managers of Islamic banks in allocating funds to different modes and portfolios for optimal returns. They may also have a big impact on the ability of policymakers to create policies appropriate for interest-free windows and branches. Moreover, they would allow Islamic banks to retain their competitive edge and improve the quality of their services.